Impact of the interest rate ceiling on the sustainability of microfinance institutions in Cambodia - ROEUNG, Sovannara (KDI School, 2018)
The main objective of this paper was to assess the impact of interest rate ceiling policy on sustainability of MFIs in Cambodia. This study covered the data analysis of Microfinance Institutions (MFIs) which have been operated from 2014 to 2017. This research used descriptive statistic to compare the trend of several critical variables related to sustainability and interest rate to make a comparison before and after the policy is implemented. In addition, the correlation coefficient was also employed to find out the relation between several critical variables. The findings of this research claimed that the policy had the negative impact on the sustainability of MFIs. In addition, high total cost of lending, mainly due to high operating cost, also lowered the sustainability of MFIs in Cambodia.
Thesis(Master) --KDI School:Master of Development Policy,2018